Cognitive antecedents of business models: Exploring the link between attention and business model design over time. Issue 3 (June 2019) - Frankenberger, Karolin; Sauer, Roman
Abstract: A firm's ability to conceive performance-enhancing business models (BMs) has become a cornerstone of competitive advantage. There is consensus that external triggers spur such BM change, but the literature has remained silent on the role of internal and cognitive antecedents such as managerial attention. In our inductive case study of four corporate spin-offs, we find that top management teams (TMTs) with a specific set of attention patterns are more likely to develop performance-enhancing BM designs. However, our findings provide evidence that specific attention foci are not sufficient to enhance particular BM designs, as it is also a matter of the intensity of attention. We further find that, over time, TMTs attention patterns shift and cause changes in BM designs. The emergent theoretical framework highlights that attention is an antecedent in explaining BM designs.